Comparison of Bronchial Lavage Cultures Taken During Endobronchial Ultrasonography in Patients with Malignant and Non-malignant Lung Diseases - Sibel Doğru; Saliha Gökçe Alagöz (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
Aim Airway pathogens have become an increasingly important concern in patients with lung diseases owing to the widespread use of immunosuppressive therapies. However, limited data are available regarding airway pathogens and antibiotic resistance in bronchial lavage (BL) cultures obtained during endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA).Materials and Methods This single-center, retrospective, cross-sectional study included 347 consecutive patients who underwent microbiological analysis of BL specimens obtained during EBUS-TBNA for the evaluation of suspected malignant or non-malignant lung disease. Clinical and microbiological characteristics were analyzed.Results The culture positivity rate of BL specimens obtained during EBUS-TBNA was significantly higher in patients with malignant lung disease than in those with non-malignant lung disease (19.2% vs. 5.4%). Among patients with malignant disease, culture positivity was significantly higher in smokers than in non-smokers (25.9% vs. 13.9%, respectively). In patients with non-malignant disease, culture positivity was 0%, 12.5%, and 15.9% in those with lymphadenopathy (LAP), a pulmonary mass/nodule, and both a mass/nodule and LAP on chest computed tomography (CT), respectively (p=0.01, p=0.192, and p=0.01). In patients with malignant disease, the corresponding culture positivity rates were 12.5%, 46.2%, and 18.6%, respectively (p=0.22, p=0.01, and p=0.738). The proportion of isolates resistant to at least one antibiotic was significantly higher in patients with malignant disease than in those with non-malignant disease (80% vs. 20%, p=0.01), whereas resistance to at least two antibiotics was observed only in patients with malignant disease (56% vs. 0%).Conclusions These findings may help clinicians identify patients in whom microbiological examination of BL samples obtained during EBUS-TBNA should be considered.